2021
DOI: 10.1177/1096348020988328
|View full text |Cite
|
Sign up to set email alerts
|

Does Sustainable Tourism Development Enhance Destination Prosperity?

Abstract: Prosperity is one of the five critical areas for Sustainable Development according to the 2030 Agenda. This research develops a prosperity model for a tourism destination and examines stakeholders’ perception of the role of sustainable tourism development in enhancing the prosperity. A set of 18 sustainability indicators were used and identified through a hybrid model that combines results from a systematic literature search and four-stage convergent interviews. Results from 171 participants from five differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 95 publications
(111 reference statements)
0
13
0
2
Order By: Relevance
“…Therefore, a tourismreliant economy should develop sustainable tourism to meet residents' needs. Falatoonitoosi et al [82] revealed that STD positively links to environmental quality, sociocultural empowerment, economic growth, quality of life, and tourist satisfaction. STD provides better tourism experience and promotes tourist-resident cooperation.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Therefore, a tourismreliant economy should develop sustainable tourism to meet residents' needs. Falatoonitoosi et al [82] revealed that STD positively links to environmental quality, sociocultural empowerment, economic growth, quality of life, and tourist satisfaction. STD provides better tourism experience and promotes tourist-resident cooperation.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In practice, the economic dimension has received more consideration from decision makers (Elgammal, 2009; Weaver, 2009) due to its obvious outcomes related to reducing poverty, and generating income and job opportunities (Abdelaziz et al , 2021; Shafaei et al , 2015). Socially, STD contributes to residents’ quality of life, in parallel to creating job opportunities while providing high-quality experiences for visitors (Hall and Lew, 1998; Falatoonitoosi et al , 2021; Mathew and Nimmi, 2021). Interestingly, some locally owned businesses implement more sustainable practices than they report or communicate to other stakeholders, which has been termed “greenhushing” (Font et al , 2017), and this leads to an underestimation of the community’s ability to implement STD.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…local communities) (Elgammal, 2009). More recent studies have developed additional STD models to explore stakeholders’ perceptions of the relationship between STD and the general enhancement of destination prosperity; findings revealed the strength of such a relationship (Falatoonitoosi et al , 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, a través de su consumo individual y por medio de diferentes asociaciones participan e intervienen en la gestión turística para lograr actuaciones empresariales más sostenibles y para lograr normas, estrategias y políticas más proteccionistas del entorno natural y social (Menconi et al, 2017) y, así, mejorar su calidad de vida. Además, al hacerlo no solo aumenta la calidad de vida local, sino también la satisfacción del turista y la prosperidad local (Mathew y Sreejesh, 2017;Falatoonitoosi et al, 2021). En este sentido, la comunidad local apoya el desarrollo de un turismo sostenible al ser percibido como una forma de turismo que ayuda a preservar los recursos naturales y que actúa como herramienta del desarrollo social local.…”
Section: Ecosistemas Turísticos Sosteniblesunclassified